The effectiveness of body language as a storytelling tool in narrative comics - Poblete, F. Catherine C. (2013)
The research problem was this: How does the visual representation of body language facilitate effective storytelling in a narrative comic? Until recently, both body language (or kinesics) and comics have experienced a dearth in scholarly focus. In the image-oriented realm of contemporary mass media, the visual nature of kinesics and comics is in need of closer study than ever. The conclusions of the overall study are as follows: a) The visual representation facilitates both the understanding and emotional response of a reader; b)The manipulation of the verbal context has more noticeable effects on a reader's understanding of a story than the manipulation of the narrative context, which produces more consistent, but less extreme results; c) Context is the most vital consideration in both direct kinesic communication as well as storytelling in comics stories; d) Well-nuanced cartooning has been established as the most effective visual technique in aiding understanding and emotional response of a reader. Exaggeration and symbolism help with the identification of emotions but do not always improve a reader's emotional response.
"April 2013"
Thesis (BFA)--University of the Philippines Diliman.
Keywords: Comic books, strips, etc; Body language in art